SOFIA/HAWC+ Far-infrared Polarimetric Large-area CMZ Exploration Survey. IV. Relative Magnetic Field Orientation throughout the CMZ - Dylan M. Paré; David T. Chuss; Kaitlyn Karpovich; Natalie O. Butterfield; Jeffrey Inara Iuliano; Xing Pan; Edward J. Wollack; Qizhou Zhang; Mark R. Morris; Mathilda Nilsson; Roy J. Zhao (The Astrophysical Journal)
The nature of the magnetic field structure throughout the Galactic Center (GC) has long been of interest. The recent Far-InfraREd Polarimetric Large-Area Central Molecular Zone (CMZ) Exploration (FIREPLACE) Survey reveals preliminary connections between the seemingly distinct vertical and horizontal magnetic field distributions previously observed in the GC. We use the statistical techniques of the Histogram of Relative Orientation and the Projected Rayleigh Statistic to assess whether the CMZ magnetic field preferentially aligns with the structure of the CMZ molecular clouds or the morphology of the nonthermal emission of the GC nonthermal filament (NTF) population. We find that there is a range of magnetic field orientations throughout the population of CMZ molecular clouds, ranging from parallel to perpendicular orientation. We posit these orientations depend on the prevalence of gravitational shear in the GC, in contrast with what is observed in Galactic Disk star-forming regions. We also compare the magnetic field orientation from dust polarimetry with individual prominent NTFs, finding a preferred perpendicular relative orientation. This perpendicular orientation indicates that the vertical field component found in the FIREPLACE observations is not spatially confined to the NTFs, providing evidence for a more pervasive vertical field in the GC. From dynamical arguments, we estimate an upper limit on the magnetic field strength for this vertical field, finding B ≤ 4 mG. A field close to this upper limit would indicate that the NTFs are not local enhancements of a weaker background field and that the locations of the NTFs depend on proximity to sites of cosmic-ray production.